(„Ich grolle nicht” w „Cudzoziemce” Marii Kuncewiczowej. O pieśni z perspektywy interdyscyplinarnej - Sokalska, Małgorzata (Studia Europaea Gnesnensia, 2014)
The paper focuses on the song as a syncretic, literary-musical genre. The appearance of song quotes in a novel (Cudzoziemka by Maria Kuncewiczowa) represents an interesting case, which may nevertheless be examined from purely literary perspective. However, a more profound interdisciplinary reading, which combines the elements of analysis of a piece of prose and a piece of music, enables a better interpretation of this particular motif in the novel.